Workers' views on involving significant others in occupational health care: a focus group study among workers with a chronic disease. Issue 26 (18th December 2022) - Snippen, Nicole C.; de Vries, Haitze J.; Bosma, Astrid R.; van der Burg-Vermeulen, Sylvia J.; Hagedoorn, Mariët; Brouwer, Sandra
Abstract: Purpose: To explore workers' views and considerations on involving their significant others (SOs) in occupational health care. Methods: Four focus group interviews in the Netherlands, with 21 workers who had visited an occupational health physician (OHP) due to work absence caused by a chronic disease. Data was analyzed using thematic analysis. Results: We distinguished four main themes: (i) attitudes towards involving SOs, (ii) preferences on how to involve SOs, (iii) benefits of involving SOs, and (iv) concerns with regard to involving SOs. Workers expressed both positive and critical opinions about involving SOs in occupational health care. Benefits mentioned included provision of emotional and informational support by SOs before, during, and after consultations. According to workers, support from SOs can be enhanced by informing SOs about re-integration plans and involving them in decision making. However, workers were concerned about overburdening SOs, and receiving unwanted support from them. Conclusions: According to interviewed workers, engagement of SOs in occupational health care can help workers with a chronic disease in their recovery and return to work. However, they felt it is important to take SO characteristics and the worker's circumstances and preferences into account, and to balance the potential benefits and drawbacks of involving SOs. Implications for rehabilitation: This study suggests that the worker's re-integration process could benefit from informing significant others about the return to work plans, involving them in decision-making, and explicitly discussing how the significant other can support the worker. Occupational health physicians have an important role in informing workers about the possibility and potential benefits of involving their significant others in the re-integration process. The involvement of a significant other in the re-integration process needs to be tailored to the specific situation of the individual worker, taking into account the preferences of both the worker and significant other. Findings suggest that it is important that occupational health physicians, workers and significant others are not only aware of the possible benefits of significant other involvement, but also of potential drawbacks such as interference during consultations, overburdening significant others, and significant others providing unwanted support.